Innovative Conservation Cropping Systems and Practices (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue “Innovative Conservation Cropping Systems and Practices” is focused on the development and assessment of innovative conservation cropping systems and practices in determining system productivity and enhancing crop production and soil quality. It covers applied engineering for achieving a sustainable balance between productivity, environmental, and profitability factors, presenting a collection of research articles that cover a broad range of cropping systems and practices from the farmland ecosystem.